2018
DOI: 10.3390/nu10101450
|View full text |Cite
|
Sign up to set email alerts
|

Mitigated Impact of Provision of Local Foods Combined with Nutrition Education and Counseling on Young Child Nutritional Status in Cambodia

Abstract: Background: In Cambodia, stunting and wasting affect, respectively, 32% and 10% of children 0–59 months while 55% are anemic. Our research aims to assess the efficiency of two local foods combined with nutritional education and counseling (CEN) activities as compared to CEN alone on improving child nutritional status and dietary intake. Methods: A cluster-randomized controlled trial was conducted in Soth Nikum area over a six-month period among children 6–23 months (n = 360) assigned to receive either moringa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 24 publications
3
63
0
3
Order By: Relevance
“…Results of our research conducted in Soth Nikum district of Siem Reap province have also shown that the quality of the 6–23 months old child diet is limited, while only a few appeared to be healthy. In particular, data have revealed that energy, iron, and zinc requirements were not fulfilled, while the degree of satisfaction of protein requirements exceeds almost double the needs [11]. These findings are in accordance with others, which revealed inadequate nutrient intakes (especially iron and zinc) among Cambodian children [12,13,14].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Results of our research conducted in Soth Nikum district of Siem Reap province have also shown that the quality of the 6–23 months old child diet is limited, while only a few appeared to be healthy. In particular, data have revealed that energy, iron, and zinc requirements were not fulfilled, while the degree of satisfaction of protein requirements exceeds almost double the needs [11]. These findings are in accordance with others, which revealed inadequate nutrient intakes (especially iron and zinc) among Cambodian children [12,13,14].…”
Section: Introductionsupporting
confidence: 73%
“…The UNICEF conceptual framework of malnutrition is used for this purpose [3]. This paper complements our previous publication which has shown that nutritional status, dietary intake and health status of young children living in Soth Nikum district were not optimal [11].…”
Section: Introductionmentioning
confidence: 93%
“…A study on the Philippines conducted by Serafico et al [96] found no significant effects of snack foods enriched with 3g MLP on Hb, weight or height after 120 days in 8 to 10 year old underweight school children (mean baseline Hb of 12.5g/dl for IG n=61/CG n=60, respectively). Similarly, in a trial by Menasria et al [95] (assigning its subjects during analysis in the categories "actual intervention received" and "non-compliers", thus not following the intention-to-treat approach), the application of 16g MLP over six months showed no significant effects on Hb, Ferritin, HAZ or WHZ in Cambodian children aged 6 to 23 months as opposed to the CG (baseline Hb 10.1g/dl, n=39 (IG) versa 9.9g/dl, n=79 (CG)). Hb increases accounted for 0.5g/dl (IG) and 0.4g/dl (CG).…”
Section: Nutrition Intervention Studies Including the Feeding Of Morimentioning
confidence: 84%
“…Indigenous nutrient-rich plant sources like Moringa oleifera are increasingly discussed as potential sustainable solution to combat malnutrition in children [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102]. Descriptive studies (intra-group comparisons) comment positively on MLP application as preventive or treatment approach however bear distinct limitations:…”
Section: Nutrition Intervention Studies Including the Feeding Of Morimentioning
confidence: 99%
“…As a dense source of micronutrients, vitamins and fatty acids, edible insects, in this instance crickets, may offer a viable alternative to protein sources that are traditionally used to treat malnutrition [37,38]. Furthermore, crickets alongside other types of edible insects, including palm weevil larvae and termites, can provide a socially acceptable food source for communities, women and children who are at a high risk of undernutrition [29,39,40]. In this context, edible insects may provide a novel approach to securing adequate food resources, while offering an opportunity to combat unsustainable food production made worse by the growing pressures of climate change [10].…”
Section: Plos Onementioning
confidence: 99%